A proteção jurídica dos “refugiados ambientais” nas três vertentes da proteção internacional da pessoa humana - Claro, Carolina de Abreu Batista (2020)
The three pathways for the international protection of the human person, consisting of International Human Rights Law, International Humanitarian Law and International Refugee Law, do not have specific rules to protect “environmental refugees”. However, these three international regimes can be applied to environment-induced migrants if they find themselves in situations recognized by these sets of rules. Using bibliographical and documental research methods, this article examines the ways in which these three areas of international law contribute to protect and recognize the rights of “environmental refugees”.